2016
DOI: 10.1039/c6ra08063d
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between carisoprodol and bovine serum albumin and effect of β-cyclodextrin on binding: insights from molecular docking and spectroscopic techniques

Abstract: Biomolecular interaction of carisoprodol (CAP) with bovine serum albumin (BSA) has been studied by fluorescence and UV-visible spectroscopy and confirmed by multispectroscopic methods including molecular docking studies. The intrinsic intensity of BSA was quenched by dynamic quenching mechanism. The binding constant and number of binding sites were calculated according to Stern-Volmer equation. Effect of β-Cyclodextrin on the binding has been studied. Thermodynamic parameters were calculated which reveal the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…The smaller K SV and K b values in the presence of β-CD for the HSA−OLA-NBD binding association indicate that β-CD prevents the direct collision of OLA-NBD molecules with HSA by forming an inclusion complex. 62,63 It also implies that OLA-NBD molecules are progressively unsheathed from β-CD by HSA to accomplish its medicinal outcome upon binding with protein. 58,62−64 HSA−OLA-NBD Association Kinetics.…”
Section: Acs Applied Bio Materialsmentioning
confidence: 59%
See 1 more Smart Citation
“…The smaller K SV and K b values in the presence of β-CD for the HSA−OLA-NBD binding association indicate that β-CD prevents the direct collision of OLA-NBD molecules with HSA by forming an inclusion complex. 62,63 It also implies that OLA-NBD molecules are progressively unsheathed from β-CD by HSA to accomplish its medicinal outcome upon binding with protein. 58,62−64 HSA−OLA-NBD Association Kinetics.…”
Section: Acs Applied Bio Materialsmentioning
confidence: 59%
“…The calculated K SV and K b values from Figures S10 and S11, respectively, at 25 °C in the absence and presence of β-CD are summarized in Table . The smaller K SV and K b values in the presence of β-CD for the HSA–OLA-NBD binding association indicate that β-CD prevents the direct collision of OLA-NBD molecules with HSA by forming an inclusion complex. , It also implies that OLA-NBD molecules are progressively unsheathed from β-CD by HSA to accomplish its medicinal outcome upon binding with protein. , …”
Section: Resultsmentioning
confidence: 99%
“…3D fluorescence spectra of BSA upon adding PPF were shown in Figure . The results represented that there are three emission peaks: Rayleigh Scattering peak ( λ ex = λ em ), the emission peak of Trp and Tyr, and second order scattering peak (2 λ ex = λ em ) . Obviously, the intensity of emission peak for BSA solution (1.0 μM) gradually declined from 550.3 a.u.…”
Section: Resultsmentioning
confidence: 93%
“…It is reported that synchronous uorescence spectroscopy is frequently used to characterize the interaction between the uorescent probe and proteins, 30 because it is of great importance for providing information about the molecular environment around the uorophore molecules. 31 The synchronous uorescence spectroscopy performs the simultaneous scanning of excitation and emission spectra on a uorimeter, and xes the wavelength difference (Dl) between them. When Dl is stabilized at 15 nm, the synchronous uorescence represents the state of tyrosine residues, whereas Dl of 60 nm indicates that of tryptophan residues.…”
Section: Hsa Binding Experimentsmentioning
confidence: 99%